2018
DOI: 10.1158/1078-0432.ccr-18-0862
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analyses of Prostate Cancer Liquid Biopsies Acquired by Apheresis

Abstract: Circulating tumor cells (CTCs) have clinical relevance, but their study has been limited by their low frequency. We evaluated liquid biopsies by apheresis to increase CTC yield from patients suffering from metastatic prostate cancer, allow precise gene copy-number calls, and study disease heterogeneity. Apheresis was well tolerated and allowed the separation of large numbers of CTCs; the average CTC yield from 7.5 mL of peripheral blood was 167 CTCs, whereas the average CTC yield per apheresis (mean volume: 59… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 23 publications
(24 reference statements)
5
108
0
Order By: Relevance
“…Importantly, none of the patients experienced adverse effects (mild, moderate, or severe). It is of note that since our initial description, DLAs have been carried out in different European hospitals without adverse effects (12,13). The reported mild adverse events are mainly due to (17) and usually occur after longer periods of leukapheresis (e.g., >2-3 h).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Importantly, none of the patients experienced adverse effects (mild, moderate, or severe). It is of note that since our initial description, DLAs have been carried out in different European hospitals without adverse effects (12,13). The reported mild adverse events are mainly due to (17) and usually occur after longer periods of leukapheresis (e.g., >2-3 h).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, analyzing 5% of DLA products, which was equivalent to a median PB volume of around 60 ml, boosted already the detection probability in the M0 patients that often have less than 1,000 CTC circulating in their total blood volume (11). In addition, the large numbers of CTCs can be used to explore heterogeneity and the subclonal architecture of systemic cancer as demonstrated by Lambros and colleagues in prostate cancer (13). A glimpse on the attainable CTC counts provided our estimation of CTC counts for the whole DLA product.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extrapolation of the frequency distribution of CTC in patients with metastatic prostate cancer, breast, and colorectal cancer showed that an increase of blood volume from 7.5 ml to 600 ml >90% of patients with metastatic cancers will have CTC detected (33). However, at present the available technologies are not yet capable of isolating CTC from the complete DLA volume (34)(35)(36). This procedure baptized Diagnostic Leukapheresis indeed allows for the isolation of a substantial larger number of CTC and enables a true "liquid biopsy."…”
mentioning
confidence: 99%